2023
DOI: 10.1039/d3ta04534j
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling dual catalysis enhancement of a pyridinium-containing Zn(ii) coordination polymer in aerobic photooxidation of organic substrates and selective photoreduction of CO2

Youting Fang,
Duobin Chao

Abstract: We herein report two Zn(ii)–terpyridine coordination polymers for photoredox reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The Carbon Capture, Utilization, and Storage project is recognized globally as one of the most effective method for reducing CO 2 . For CO 2 utilization, many studies have reported on the conversion of CO 2 into value-added chemicals. Previous research studies have shown that photocatalytic CO 2 reduction reaction is a promising strategy for CO 2 utilization . The reaction has generally taken place at room temperature and under normal pressure with the aid of light and photocatalysts .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Carbon Capture, Utilization, and Storage project is recognized globally as one of the most effective method for reducing CO 2 . For CO 2 utilization, many studies have reported on the conversion of CO 2 into value-added chemicals. Previous research studies have shown that photocatalytic CO 2 reduction reaction is a promising strategy for CO 2 utilization . The reaction has generally taken place at room temperature and under normal pressure with the aid of light and photocatalysts .…”
Section: Introductionmentioning
confidence: 99%
“…3−6 Previous research studies have shown that photocatalytic CO 2 reduction reaction is a promising strategy for CO 2 utilization. 7 The reaction has generally taken place at room temperature and under normal pressure with the aid of light and photocatalysts. 8 Molecule CO 2 has a stable linear nonpolar molecular structure(ΔG f,CO 0 = −394.228 kJ/mol) and is difficult to be activated.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations